2006
DOI: 10.1068/c53m
|View full text |Cite
|
Sign up to set email alerts
|

When Frames Conflict: Policy Dialogue on Waste

Abstract: The author discusses the notion of environmental controversies as frame conflicts through a case study of the waste-policy dialogue in Finland. The argument that intractable policy controversies result from internally consistent but incompatible normative^prescriptive scripts which name and frame problems differently is explored. Different waste-policy frames are identified and it is suggested that these frames do indeed contribute to the stubbornness of ongoing debate on incineration versus waste reduction. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…Critically examining how metaphor theory can inform a range of deliberative research and policy development processes that are 'language focused' seems warranted to underpin moves towards deliberative decision making and deliberative democracy more broadly. Breaking out of deeply held patterns of understanding is however, very difficult and may be more complex than merely resolving operational frame conflicts (Saarikoski, 2006) which continue to circulate around the axes of existing metaphors.…”
Section: Resultsmentioning
confidence: 99%
“…Critically examining how metaphor theory can inform a range of deliberative research and policy development processes that are 'language focused' seems warranted to underpin moves towards deliberative decision making and deliberative democracy more broadly. Breaking out of deeply held patterns of understanding is however, very difficult and may be more complex than merely resolving operational frame conflicts (Saarikoski, 2006) which continue to circulate around the axes of existing metaphors.…”
Section: Resultsmentioning
confidence: 99%
“…-Pero también se citan a menudo otros elementos como: a) la gobernabilidad y el proceso de toma de decisiones (Dente et al, 1998;Hackel, 2001;Wolsink, 2010;Subirats, 2008: 133;Nel·lo, 2003a;Ferran, 2008: 20;CIPMA, 1995); b) los «recursos escasos» (resource conflicts), vinculados a la degradación ambiental, a la mayor demanda de recursos naturales, etc. (Redorta, 2004: 144); c) «lo distributivo», que se ha trabajado desde la economía ecológica y la ecología política (Martínez Alier y O'Connor, 1996; Walton y Barnett, 2008) y que se refiere a la inequidad en la asignación de los recursos naturales o de los costes y los beneficios de una actuación determinada (Crespo, 1999); d) la «información» como fuente de conflicto y como circunstancia que influye en el desarrollo del mismo, y e) el frame, es decir, el prisma con el que vemos, sentimos y entendemos la realidad (Saarikoski, 2006;Alfasi, 2004;Lewicki et al, 2003;Dente et al, 1998). -Prevalecen los enfoques estructuralistas, pero progresivamente va ganando terreno la escuela psicosociológica, la cual defiende que «los temas ambientales no son sólo una cuestión de intereses» (Kim, 2003: 125), sino también de significados, narrativas, actitudes, comportamiento, etc.…”
Section: Otros Aspectosunclassified
“…Además, la apuesta por una lógica de negociación de suma positiva (win-win) y la aceptación de que frecuentemente los conflictos son de «suma variable» (Entelman, 2002) no ha impedido que, a menudo, en los conflictos ambientales y territoriales catalanes, la negociación se entienda como un «reparto del pastel […] negán-dose el carácter creativo y transformativo del conflicto» (Direcció General de Participació Ciutadana, 2007: 15). Por otro lado, se olvida que no siempre los intereses en competencia están tan claros, que pueden haber puntos de partida distintos que no permitan el intercambio (Saarikoski, 2006) o que no todos los actores tienen acceso a la negociación.…”
Section: Enfoques Y Métodos Primariosunclassified
“…At the time, different stakeholders saw the project type and its role amongst other management options as controversial, and discussions about its effects often resulted in conflicting views; the projects were seen as both harmful and beneficial Saarikoski 2006). Saarikoski (2006) has suggested that opponents and proponents of waste incineration had a fundamental difference in focus, the former wanting to address the question of waste minimization, with the latter already focused on incineration as an appropriate waste management option. As such, the situation could be considered a classic example of a situation where the whole justification of a project is questioned.…”
Section: Impact Assessment and Project Appraisalmentioning
confidence: 99%